Classroom Management for Prospective Elementary School Teachers - Ismanto, Ismanto (PPSDP International Journal of Education, 2025)
This study aims to explore the classroom management practices of student teachers in the Elementary School Education (PGMI) Study Program at the Faculty of Tarbiyah IAIN Kudus. This research uses a case study approach, involving students of the PGMI Study Program at the Faculty of Tarbiyah IAIN Kudus in conceptual and practical learning related to classroom management. Data collection was carried out using semi-structured interview techniques with student participants regarding the experience of classroom management practices, passive observation presented in the form of visual micro-teaching practices and field experience practices, as well as documentation of the study program curriculum which contains a cluster of classroom management courses. While analyzing the data of this study using thematic analysis. The findings of this study explore that the readiness of PGMI IAIN Kudus study program students in micro-teaching practice as a forum for how practitioners simultaneously and alternately play roles, both as teachers, students, and even observers (observers, supervisors), while PPL as a forum for real practice and self-development in the frame of education, both formal, non-formal, and informal become a reality.